Review and Assessment of Energy Policy in the Economic Community of West African States region - Mewenemesse, Herve Tevenim; Yan , Qiang (International Journal of Energy Economics and Policy, 2022)
The ECOWAS region has one of Africa’s highest potentials for energy production, including both non-renewable (oil, gas, and uranium) and renewable sources (hydroelectric, solar energy, wind energy). Despite this significant potential, the region deals with a number of issues that affect its energy strategy. A review and analysis of the social, political, and economic factors influencing regional energy policy are provided in this paper, along with an assessment and forecast of energy policy in the ECOWAS. The analysis of regional energy policy then takes into account demand management, clean energy production, regional energy trade, and hydrocarbon exploration and production. The results show that the ECOWAS nations have started their transition to a renewable energy-based economy. These policies have long-term implications on the world’s energy system and have the potential to improve the region’s energy policy, even if the consequences are not immediately noticeable.